2012
DOI: 10.1051/0004-6361/201219004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances of distant extremely metal-poor unevolved stars

Abstract: Context. The old Galactic halo stars hold the fossil record of the interstellar medium chemical composition at the time of their formation. Most of the stars studied so far are relatively near to the Sun, this prompts the study of more distant stars, both to increase the size of the sample and to search for possible variations of abundance patterns at greater distances. Aims. The purpose of our study is to determine the chemical composition of a sample of 16 candidate extremely metal-poor (EMP) dwarf stars, ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 53 publications
4
94
0
1
Order By: Relevance
“…Edvardsson et al 1993). As discussed in Caffau et al (2013) the microturbulence values derived in the studies of Bonifacio et al (2012) and Sbordone et al (2010), which cover stars similar to the ones considered here, suggest that fixing the microturbulence for all stars at 1.5 km s −1 is reasonable, and we followed this approach here. A summary of the stellar parameters of the sample of stars is available in and Ca were derived with the code MyGIsFOS (Sbordone et al 2013), based on the OSMARCS-turbospectrum grid of synthetic spectra, and are shown in Table 3.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Edvardsson et al 1993). As discussed in Caffau et al (2013) the microturbulence values derived in the studies of Bonifacio et al (2012) and Sbordone et al (2010), which cover stars similar to the ones considered here, suggest that fixing the microturbulence for all stars at 1.5 km s −1 is reasonable, and we followed this approach here. A summary of the stellar parameters of the sample of stars is available in and Ca were derived with the code MyGIsFOS (Sbordone et al 2013), based on the OSMARCS-turbospectrum grid of synthetic spectra, and are shown in Table 3.…”
Section: Discussionmentioning
confidence: 96%
“…Our project is a spin-off of a pilot survey conducted using French and Italian guaranteed observing time on X-Shooter: a sample of twelve stars has previously been analysed by Bonifacio et al (2011);Caffau et al (2011bCaffau et al ( ,c, 2012, and Caffau et al (2013). In addition, other useful data for our purposes can be found in Bonifacio et al (2012), who analysed 16 EMP stars observed with UVES that were selected in a similar manner from SDSS; Spite et al (2013), who analysed three stars selected because they were C-enhanced; and Behara et al (2010), who analysed another set of three C-enhanced stars extracted from the SDSS. In an effort parallel to our own, the team led by W. Aoki has observed 137 metal-poor and extremely metal-poor stars extracted from the SDSS with HDS at the 8.2 m Subaru telescope (Aoki et al 2013).…”
Section: Topos Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although followup high-resolution spectroscopy of likely VMP/EMP stars from SDSS/SEGUE has only recently begun (e.g., Caffau et al 2011b;Bonifacio et al 2012;Aoki et al 2013), the SDSS/SEGUE sample has already resulted in the discovery of several stars in the ultra metal-poor (UMP; [Fe/H] < −4.0) range, SDSS J102915 + 172927, with [Fe/H] = −4.73 (Caffau et al 2011a), SDSS J144256 + 253135, with [Fe/H] = −4.09 (Caffau et al 2013), and another star, SDSS J174259 + 253135, for which iron lines could not be measured, but with [Ca/H] < −4.5 (Caffau et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the numbers of stars with confirmed metallicities of [Fe/H] < −3.0 was relatively small, making it difficult to infer the global characteristics of EMP stars. Since 2005, more than 200 stars with [Fe/H] < −3.0 have been confirmed, based on high-resolution spectroscopic analyses (e.g., Barklem et al 2005;Caffau et al 2013a,b;Yong et al 2013), including more than 50 stars with [Fe/H] < −3.5, and over 20 with [Fe/H] < −4.0 (Barklem et al 2005;Frebel et al 2005Frebel et al , 2015Cohen et al 2008;Caffau et al 2011aCaffau et al ,b, 2012Bonifacio et al 2012;Aoki et al 2013;Caffau et al 2013b;Spite et al 2013;Yong et al 2013;Keller et al 2014;Allende Prieto et al 2015;Li et al 2015;Placco et al 2015;Meléndez et al 2016).…”
Section: Introductionmentioning
confidence: 99%